1972
DOI: 10.1139/v72-455
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygenation of 2-Oxazolin-5-ones: A New Synthesis of Imides

Abstract: In the presence of mild base such as triethylamine, the two 4-alkylidene-2-phenyI-2-oxazolin-5-ones, 1 and 8, rapidly absorb oxygen at room temperature with the loss of carbon dioxide and the formation of the imides 4 and 10. The imide probably arises by decomposition of a hydroperoxide resulting from the reaction of oxygen and the anion of the oxazolinone. A hydroperoxide intermediate will also account for the origin of the acidic by-products 6 a and l l a . The 2-methyl-2-oxazolin-5-one 14 did not react with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…70-75% yield.362 Fissekis et al have shown that cycloalkylglyoxylic acids (C6 and C5 rings) readily react with 4,5,6-triaminopyrimidine(225) in strong acid to yield 4amino-6-cycloalkyl-7-hydroxypteridines(226a,b)…”
mentioning
confidence: 99%
“…70-75% yield.362 Fissekis et al have shown that cycloalkylglyoxylic acids (C6 and C5 rings) readily react with 4,5,6-triaminopyrimidine(225) in strong acid to yield 4amino-6-cycloalkyl-7-hydroxypteridines(226a,b)…”
mentioning
confidence: 99%